Scan Performance and Reconfigurability of Agile Radiating Matrix Antenna Prototype - H. Abou Taam; G. Zakka El Nashef; M. Salah Toubet; E. Arnaud; B. Jecko; T. Monediere; M. Rammal (International Journal of Antennas and Propagation)
This paper is dedicated to different experimental validations concerning a novel concept of beam forming and beam steering antenna. The working principle of the antenna is based on the equivalent radiating surface approach and inspired from an electromagnetic band gap antenna. The theoretical aspect and some numerical validations have been already published in the work of Abou Taam et al. (2014). Different electromagnetic behaviors have been demonstrated, such as low mutual coupling, and high gain preservation for high scanning angles values. In this paper, some of these electromagnetic behaviors will be proven experimentally by the means of two different feeding configurations.